The everything guide to narcissistic personality disorder : professional, reassuring advice for coping with the disorder : at work, at home, and in your family - Goodman, Cynthia Lechan; Leff, Barbara (Avon, Mass. : Adams Media, 2012)
"Narcissistic personality disorder, often mistaken for a too-big ego or inflated self-esteem, is in actuality a severe psychological condition that ruins marriages, social relationships, work environments, and often your own sense of self. Although many narcissists may be perceived as self-confident and arrogant, if you suffer from this disorder, you may fall victim to devastatingly low self-esteem and insecurity. ... [W]ith an exclusive section on the epidemic of 'net narcissism' due to social media"--P. [4] of cover.
The top 10 signs of narcissistic personality disorder -- The basics of narcissistic personality disorder (NPD) -- Symptoms and behaviors of NPD -- Comparing NPD to other personality disorders -- Who are the narcissists? -- What can lead to narcissism? -- Treatments for NPD -- Additional methods for dealing with NPD -- What happens without treatment -- Asking for help when dealing with a narcissist -- Exploring myths and lifestyles -- Tools and coping techniques -- Understanding megalomania -- Narcissism and depression -- Changing perspectives of the relationships -- The digital narcissist -- If you believe someone needs help with NPD -- Living every day with someone who has NPD -- Handling interactions with a narcissist -- Ongoing controversies -- Where do you go from here?
Includes bibliographical references (p. 281-283) and index.
Keywords: Narcissism -- Popular works; Personality disorders -- Popular works